COVID-19 - the challenge to treat a disease and not a positive RT-PCR test - Maria Georgieva Moneva-Sakelarieva; Yozlem Ali Kobakova; Petar Yordanov Atanasov; Danka Petrova Obreshkova; Stefka Achkova Ivanova; Evgenia Kirilova Stankova (Pensoft Publishers, 2021)
The new pandemic disease COVID is quick spread worldwide.The primary method used for diagnosing of COVID-19 is detecting viral nucleic acids. The main problem with RT-PCR test is the false negative results. The negative RT-PCR does not exclude a SARS-CoV-2 infection and this method should not be used as the only diagnostic criteria. The RT-PCR result does not change the complex treatment of the disease. The aim of the current study is to compare the four groups clinical cases of the different parameters: RT-PCR test, rapid test, clinical picture, laboratory tests as hematology, inflammatory markers, coagulation status and chemistry and imaging examinations: Chest X-ray at and Chest CT scan. Complex therapeutic approach has been implemented: antibiotic, inflammatory, anticoagulants, oxygen therapy, hepatoprotectors, antimycotics, fibrinolytics, probiotics, essential oils, vitamins. During the follow-up period, a tendency for significant reduction and resorption of the pulmonary changes on the CT scans has been seen.